Traumatic brain injury identification processes for school-aged children in rural Colorado school districts - Palmer, Maureen K., author; Sample, Pat L., advisor; Greene, David, committee member; Daunhauer, Lisa, committee member (Colorado State University. Libraries, 2016)
Rationale: Recent changes in Colorado legislation have led to the implementation of new procedures in identification and classification of students with traumatic brain injury (TBI). The purpose of this study was to highlight changes to TBI identification protocols and subsequent approbation of services in rural Colorado schools since the change in state requirements. Methods: The study employed a case study design. Data collection measures included focus groups and interviews with participants, field observations, transcription, coding and triangulation. Results: Six patterns emerged from data analysis which spoke to current TBI identification and service delivery protocols in schools: (1) geographic limitations (2) waves of administrative support, (3) low socioeconomic status, (4) fragmented communication, (5) school professionals' perceptions of TBI and (6) cultural attributes of the rural location. Discussion: Influential patterns present in rural districts lend insight into barriers to implementation of TBI identification and service delivery. Recommendations for improved service delivery in rural areas focus on increasing access of school personnel to professional development as well as state protocols that can facilitate communication between state and local education agencies. These findings in rural Colorado illuminate barriers to TBI service delivery and can be factors to consider for other states attempting to implement new best practices for students with TBI.